Problem Analysis Of Inquiry Learning Model Devices That What Happens In Chemistry Teacher At SMAN Samarinda - Maradona -; Makrina Tindangen; Erwin - (PROSIDING SEMINAR KIMIA, 2015)
This study aims to determine the problem of Inquiry Learning Devices Model Happens in High School Chemistry Teacher in Samarinda. Subjects in this research were 1 teacher and 1 respondents.Methods of analysis was done qualitatively obtained through observation, interviews, documentation and triangulation and data obtained in the research then described.The results showed that the chemistry teacher is having problems in the preparation of RPP learning device.